2014
DOI: 10.1016/j.annfar.2013.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Does sevoflurane preserve regional cerebral oxygen saturation measured by near-infrared spectroscopy better than propofol?

Abstract: Cerebral cortical oxygenation measured by NIRS may be better preserved with sevoflurane than with propofol. These findings suggest that sevoflurane anaesthesia could be a good option in patients with compromised cerebral oxygenation, given the absence of intracranial hypertension. Further studies with larger sample sizes are required to support our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…23,24 An additional nine RCTs were excluded as they did not involve the target intervention comparison. [25][26][27][28][29][30][31][32][33][34] Two additional RCTs were excluded because they were published as an abstract 35,36 and one RCT was excluded because although it correlated anesthetic depth with cerebral oximetry, it did not detail the associated intervention. 37 Finally, three additional trials were identified from reference lists of the articles included.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…23,24 An additional nine RCTs were excluded as they did not involve the target intervention comparison. [25][26][27][28][29][30][31][32][33][34] Two additional RCTs were excluded because they were published as an abstract 35,36 and one RCT was excluded because although it correlated anesthetic depth with cerebral oximetry, it did not detail the associated intervention. 37 Finally, three additional trials were identified from reference lists of the articles included.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…Initial studies of fNIRS parameters during maintenance focused on examining differences in rSO 2 and CBF between anesthetics to understand the effect of anesthetics on the oxygen supply demand balance and metabolism. Differences in oxygen saturation on the frontal cortex were found between sevoflurane and propofol during maintenance of anesthesia [ 37 ]. Sevoflurane was found to produce higher rSO 2 values, which indicated that sevoflurane at 1.5% maintains the CBF/CMRO 2 coupling to a similar extent as propofol [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Differences in oxygen saturation on the frontal cortex were found between sevoflurane and propofol during maintenance of anesthesia [ 37 ]. Sevoflurane was found to produce higher rSO 2 values, which indicated that sevoflurane at 1.5% maintains the CBF/CMRO 2 coupling to a similar extent as propofol [ 37 ]. Measurements of rSO 2 have also been used to evaluate the incidence of cerebral desaturation events during surgical procedures [ 37 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In situations of raised ICP (e.g., brain tumors), research with volatile anesthetics have shown that they may maintain a significantly higher SjO 2 compared with propofol [22]. Further, in the supine position for normal surgery [23], in the sitting position for arthroscopy [13], and during one-lung ventilation for lung surgery [24], volatile anesthetics can maintain higher cerebral oxygenation than propofol. One pilot study has reported that, compared with sevoflurane, propofol increased cerebral SctO 2 only when the stimulus of surgery was intense [25].…”
Section: Discussionmentioning
confidence: 99%